GLOBALISASI DAN TRANSFER TEKNOLOGI: PENOPANG INDUSTRI MANUFAKTUR PADA PERKEMBANGAN MARKETPLACE DI REGIONAL ASEAN - Anung - Riyanti; Nelin Dias Pratiwi; Nadya Yolanda Nainggolan; Nabilla Rachma Sardi; Alexander Bayu Satrya (Review of International Relations, 2021)
In recent years, globalization has brought about significant changes in information and communication technology, particularly in the use of the internet in the economic field. Globalization is often seen as a phenomenon that creates socio-economic disparities and harms developing countries. The manufacturing industry has started to digitize marketing, not stopping at the creation of web-commerce, but also starting to appear unicorns known as marketplaces. The marketplace is present as evidence of business modernization, facilitating the process of product marketing, distribution and consumption. This paper uses a qualitative descriptive approach by applying the conceptual framework of globalization and modernization. The author presents the concepts of technology transfer and economic liberalization. The author analyzes based on grouped data about the role of the marketplace in the manufacturing industry in Southeast Asia. The author argues that globalization brings technology transfer which ultimately creates a marketplace largethat contributes to increased production in the manufacturing industry. Therefore, globalization does not only have a bad impact, on the contrary, if people are able to keep up with existing developments, it will be able to provide opportunities and benefits in economic life in Southeast Asia.  Keywords: globalization, technology transfer, marketplace, ASEAN